Distribution of Air Embolization During TEVAR Depends on Landing Zone: Insights From a Pulsatile Flow Model. (August 2019) - Makaloski, Vladimir; Rohlffs, Fiona; Trepte, Constantin; Debus, E. Sebastian; Øhlenschlaeger, Bent; Schmidli, Jürg; Kölbel, Tilo
Purpose: To analyze the distribution of air bubbles in the supra-aortic vessels during thoracic stent-graft deployment in zones 2 and 3 in an aortic flow model.Materials and Methods: Ten identical, investigational, tubular, thoracic stent-grafts were deployed in a glass aortic flow model with a type I arch: 5 in zone 2 and 5 in zone 3. A pulsatile pump generated a flow of 5 L/min with systolic and diastolic pressures (±5%) of 105 and 70 mm Hg, respectively. The flow rates (±5%) were 300 mL/min in the subclavian arteries, 220 mL/min in the vertebral arteries, and 400 mL/min in the common carotid arteries (CCAs). The total amounts of air released in each supra-aortic branch and in the aorta were recorded.Results: The mean amounts of air measured were 0.82±0.23 mL in the zone-2 group and 0.94±0.28 mL in the zone-3 group (p=0.49). In the zone-2 group compared with zone 3, the amounts of released air were greater in the right subclavian artery (0.07±0.02 vs 0.02±0.02 mL, p<0.01) and right CCA (0.30±0.8 vs 0.18±07 mL, p=0.04). There were no differences between the groups concerning the mean amounts of air measured in the right vertebral and all left-side supra-aortic branches. The amount of air released in the descending aorta was significantly higher in the zone-3 group vs the zone-2 group (0.48±0.12 vs 0.13±0.08 mL, p<0.01). Small bubbles were observed continuously during deployment, whereas large bubbles appeared more commonly during deployment of the proximal stent-graft end and after proximal release of the stent-graft.Conclusion: Air is released into all supra-aortic branches and the descending aorta during deployment of tubular thoracic stent-grafts in zones 2 and 3 in an aortic flow model. Higher amounts of air were observed in right-side supra-aortic branches during deployment in zone 2, whereas significantly greater amounts of air were observed in the descending aorta during deployment in zone 3.